2007
DOI: 10.1073/pnas.0703033104
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic inhibition by a deleted in liver cancer gene requires cooperation between tensin binding and Rho-specific GTPase-activating protein activities

Abstract: The three deleted in liver cancer genes (DLC1-3) encode RhoGTPase-activating proteins (RhoGAPs) whose expression is frequently down-regulated or silenced in a variety of human malignancies. The RhoGAP activity is required for full DLC-dependent tumor suppressor activity. Here we report that DLC1 and DLC3 bind to human tensin1 and its chicken homolog. The binding has been mapped to the tensin Src homology 2 (SH2) and phosphotyrosine binding (PTB) domains at the C terminus of tensin proteins. Distinct DLC1 seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
243
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(251 citation statements)
references
References 28 publications
7
243
0
1
Order By: Relevance
“…Liver cancer cell lines without endogenous DLC-1 gene expression was transfected by DLC-1 cDNA, confirmed DLC-1 gene expression has an inhibitory effect on liver cancer cells growth (Zhou et al, 2004). In addition, the same results were also obtained from the lung cancer, breast cancer cell lines and nasopharyngeal carcinoma (NPC) (Yuan et al, 2004;Plaumann et al, 2003;Qian et al, 2007;Seng et al, 2007). transfected DLC-1 into two DLC-1 negative breast cancer cell lines, and found cell proliferation rate declined obviously, and further the DLC-1 negative cells and DLC-1 trasfected cells were injected into the nude mouse for 3 weeks, respectively, the former gradually developed into tumor, its histopathological was same as mammary gland adenocarcinoma, the latter had no tumor formation, therefore, DLC-1 play an important inhibition role in the breast cancer formation.…”
Section: Discussionsupporting
confidence: 52%
“…Liver cancer cell lines without endogenous DLC-1 gene expression was transfected by DLC-1 cDNA, confirmed DLC-1 gene expression has an inhibitory effect on liver cancer cells growth (Zhou et al, 2004). In addition, the same results were also obtained from the lung cancer, breast cancer cell lines and nasopharyngeal carcinoma (NPC) (Yuan et al, 2004;Plaumann et al, 2003;Qian et al, 2007;Seng et al, 2007). transfected DLC-1 into two DLC-1 negative breast cancer cell lines, and found cell proliferation rate declined obviously, and further the DLC-1 negative cells and DLC-1 trasfected cells were injected into the nude mouse for 3 weeks, respectively, the former gradually developed into tumor, its histopathological was same as mammary gland adenocarcinoma, the latter had no tumor formation, therefore, DLC-1 play an important inhibition role in the breast cancer formation.…”
Section: Discussionsupporting
confidence: 52%
“…DLC is a nucleocytoplasmic shuttling protein 20,23 , although this shuttling function was not affected by Ser549 phosphorylation. DLC1 interaction with tensin has been well established and is crucial for proper function of DLC1 12,[24][25][26] . Thus, we investigated whether Ser549 phosphorylation regulates the association between DLC1 and tensins.…”
Section: S549a and S549d Mutants (Supplementary Figs S4 And 5)mentioning
confidence: 99%
“…However, the activation of Rho proteins contributes to tumorigenesis and metastasis in many cancers 10 , and RhoGAP activity has a predominant role in the tumour suppressor functions of DLC1 11 . In different cell line models, ectopic expression of the RhoGAP mutant of DLC1 fails to suppress cell growth and motility 12,13 , and functional studies have shown that RhoGAP and the growth inhibitory activities of DLC1 are impaired as a result of T301K and S308I mutations, which were identified in prostate and colon cancer patients 14 . These studies suggest that RhoGAP activity and growth suppression activity are tightly associated.…”
mentioning
confidence: 99%
“…As a new member of GAP family, deleted in liver cancer 1 (DLC1) has been proved to possess RhoGAP activity (Yuan et al, 1998;Wong et al, 2003). Our previous studies show that DLC1 suppresses cancer cell migration by its RhoGAP activity (Qian et al, 2007;Li et al, 2011). In this paper, we investigated effects of H 2 O 2 on proliferation by checking cell cycle and apoptosis-related genes and explored H 2 O 2 -mediated suppression of migration via DLC1/RhoA signaling pathway.…”
Section: Introductionmentioning
confidence: 99%